Dampak Destinasi Wisata Nglinggo Tritis Kabupaten Kulon Progo terhadap Transformasi Perdesaan - Nugraha, Indra Cahya; Prameswara, Bangga; Sfarliana, Frisda (Jurnal Pariwisata Terapan, 2023)
Deagrarianization in Indonesia has been happening since the 1970's where the proportion of gross domestic product in agriculture has been surpassed by industry. Tourism is one of the non-agricultural sectors that can help rural communities who live around tourist destinations to diversify their occupation and improve their welfare. This case study was conducted in Nglinggo Tritis, Kulon Progo Regency, Yogyakarta Special Region by collecting primary data by interviewing tourist destination workers and secondary data in the form of statistics and information from online news which is described with qualitative approach. Results showed that the tourist destination impacts the economy of rural communities around the tourist destination by giving them a chance to work outside the agricultural sector.